(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
The present/actual work aims to analyze the history of the assortment of the human right to water and its normative consecration - an international level, and from that starting point, it is sought through the long struggle of the people and “La Pampa” Government, on the right that they get in the sharing use of the interprovincial river waters.